Knowledge of Cervical Cancer Prevention Among Women in Amazonian Peru - Lauren Gochenaur; Sara Peterson; Luis Vasquez; David Adler (Women's Health Reports, 2020)
Background and Purpose: Survey-based research was conducted in Yantalo, Peru, a rural Amazonian community, to assess the knowledge base among women surrounding cervical cancer, human papilloma virus (HPV), and preventative health practices as well as to gain a better understanding of barriers to accessing care. Methods: A total of 217 women were interviewed out of the 1612 female inhabitants of Yantalo utilizing a structured interview-style questionnaire with both closed and open-ended questions. Results: Our average respondent was 41.6 years old with the equivalent of some high school education. Approximately 75% of respondents reported that they had heard of HPV and/or cervical cancer, with 44.4% reporting they had received a test to check for cervical cancer within their lifetime. When given a 10-question knowledge assessment regarding safe sex practices and cervical cancer, women obtained an average score of 57.3%. When asked about receiving the HPV vaccine, 29% reported ?Yes?, 59.4% reported ?No?, and 11.6% reported ?I don't know.? Although 62.6% of women indicated that they have ?easy access to cervical cancer screening,? 37.4% of women reported experiencing at least one barrier to accessing care. The highest reported barriers include fear of the test causing them pain and/or lack of knowledge of the necessity cervical cancer testing. Cervical cancer rates in Peru are approximately three times that in developed countries. Conclusions: Gathering data surrounding knowledge and the barriers among the female population in rural communities is essential to developing targeted initiatives that address pertinent obstacles within these and other vulnerable communities.